PENERAPAN KOMBINASI METODE VIGENERE CIPHER, CAESAR CIPHER DAN SIMBOL BACA DALAM MENGAMANKAN PESAN - Hardita, Veny Cahya; Sholeha, Eka Wahyu (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
The concept that an important information cannot be known by parties who don’t have rights can be done by making the confidentiality of data using cryptography. Safety in vigenere ciphers depends on the number of keys used, the more the number of keys, the wider the key space. While caesar cipher or often also called caesar code is a classic coding system based on simple substitution. This study uses a combination of Vigenere Cipher and Caesar Cipher algorithms so that the security of the contents of the message is protected stronger and safer so that if the message sent is tapped by someone who is not responsible then the hijacker has difficulty knowing contents of the message. So that the confidentiality and authenticity of message is up to the recipient In this study successfully implemented both methods and has an output in the form of a reading symbol, not letters.